Level of financial performance of selected construction companies in South Africa - Emmanuel Dele Omopariola; Abimbola Olukemi Windapo; David J. Edwards; Hatem El-Gohary (Journal of Risk and Financial Management, 2021)
Purpose-There is no consensus on the indicators that assess a construction company's financial performance projects undertaken. There is also a dearth of concepts on the financial performance indicators for construction companies in South Africa and indeed, the wider continent of Africa. This paper proposes novel financial performance indicators for assessing construction organizations and tests these on selected construction companies in the South African construction industry. Design/methodology/approach-This research employed a pragmatic approach. Contractors with financial credibility and capacity of ÏR 40 million, annual turnover of ÏR 20 million, and available capital of ÏR 40 million were purposively selected for this study. Parameters such as total revenue, direct cost of work, total indirect cost and total income were elicited from the sample contractors to assess their financial performance. The assessment was undertaken using formulas that were formulated based on the descriptions provided under the research methodology. Further analysis was conducted using post hoc Tukey's honest significant difference (HSD). Findings-The study finds that construction companies with a strong structure, multiple areas of specialization, creative and efficient staff members, and access to funding, have a greater chance of experiencing higher: income; positive leverage; positive liquidity; and positive cash flow. Moreover, companies with specialization in civil engineering construction and project management skills experienced higher positive liquidity and profitability. Originality/value-This research is unique through its investigation and formulation of indicators for assessing the financial performance of construction companies. This research is consequently representing the first attempt to analyze financial data using the approaches prescribed and adopted.
Keywords: 330; construction organization; company size; financial performance indicators; time frame; project management